Micro-level stickiness as a threat to client centric knowledge transfer among ICT firms in Malaysian technology parks - Ismail, Yusof; Sarif, Suhaimi Mhd (IGI Global, 2012)
The study in this chapter was carried out to ascertain whether the national ICT initiative on facilitating knowledge transfer among ICT firms by providing dedicated technology parks throughout Malaysia was client centric. It examines the issue from a micro level perspective of stickiness of knowledge transfer,which includes transfer mechanisms, types of transfer, knowledge barriers, and transfer contexts. The study solicited the opinions of competent informants (i.e., policy makers and competent ICT leaders)through face-to-face interviews in three technology parks located in northern and central Peninsular Malaysia (Kulim High Technology Park; MSC,Cyberjaya; and Selangor Science Park). The results confirm the presence of stickiness in terms of mechanisms specified in the literature.